Complications of Nasoseptal Flap Reconstruction: A Systematic Review - Lavigne, Philippe; Faden, Daniel L.; Wang, Eric W.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective The nasoseptal flap (NSF) is considered the primary vascularized flap for reconstruction of dural defects with endoscopic endonasal surgery (EES) of the skull base. However, the complications and morbidities associated with this reconstructive flap are poorly understood. This article presents a systematic review of the complications and morbidities related to the use of the NSF in skull base surgery.Method A systematic review of the literature based on published guidelines was performed to identify potential complications and morbidities related to the NSF. The MEDLINE and Embase databases were searched from January 1, 1950 to February 5, 2018.Results Twenty-seven articles were identified. Reported complications were as follows: NSF necrosis (4 studies; [0–1.3%]), mucocele formation (5 studies; [0–3.6%]), septal perforation (6 studies, [0–14.4%]), nasal dorsum collapse (2 studies, [0.7–5.8%]), effects on quality of life (QoL) (8 studies), and olfactory loss (11 studies).Conclusion Although complications associated with the NSF may be underreported in the literature, the NSF appears to be a safe and reliable reconstructive flap in EES of the skull base.
Keywords: systematic review; skull base surgery; nasoseptal flap; complications; reconstruction